A textured surface spectral absorption coating for enhancing light trapping effect and preparation method thereof
Through high-temperature annealing and oxidation reaction, the textured surface is formed and the protective layer is deposited, which solves the problem of performance degradation caused by atomic diffusion and oxidation at high temperatures, and achieves efficient spectral absorption and high temperature stability, which is suitable for industrial production.
Patent Information
- Application Number
- CN202210882534.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-07-26
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2042-07-26
AI Technical Summary
The existing solar absorbent coatings have deteriorated absorption rates due to atomic diffusion and surface oxidation at high temperatures, and traditional processes are difficult to control chemical conditions and are suitable for large-scale production.
Through high-temperature annealing and oxidation reaction, high-diffusion coefficient elements in the substrate are used to diffuse to the surface and react with oxygen to form a textured surface, and an oxide layer/nitride layer/nitride oxide layer is deposited as anti-reflection and anti-oxidation layers to extend the high temperature of the coating. Stability and absorption properties.
It improves the long-term operation reliability and stability of solar absorbing coatings, extends the durability time at high temperatures, reduces reflectivity, and is suitable for industrial mass production.
Smart Images

Figure CN115642199B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of coating preparation, and in particular relates to a textured surface spectral absorption coating for enhancing light trap effect and a preparation method thereof. Background Art
[0002] Concentrating Solar Power (CSP) is the most environmentally friendly and efficient solar energy development technology with great prospects. It is being deployed globally and is expected to generate 7% of global electricity in 2030 and 25% of global electricity in 2050. Its key component is the spectral absorption surface on the photothermal converter, which converts light and heat into electrical energy and determines the working efficiency of the entire system. With the upgrade of the CSP system, the operating temperature of the solar field will increase from 400℃ to 500℃ and above. The original excellent performance of Mo-Si3N4, Mo-Al2O3, Pt-Al2O3 and other absorption coatings can no longer meet the new working standards.
[0003] The main reason is that the existing research has the following problems:
[0004] Problem 1: Atomic diffusion of the absorption sublayer (anti-reflection layer, absorption layer and infrared reflector) occurs at high temperature, which destroys the basic structure of the absorption coating and degrades the absorption rate in the solar spectrum band.
[0005] Question 2: Under high temperature outdoor environment, oxidation occurs on the surface of the absorption layer, resulting in a decrease in the reflectivity of the infrared spectrum band.
[0006] Therefore, in order to solve the problem of optical performance stability of existing absorption coatings at 500°C and above, it is necessary to start from both atomic diffusion and surface oxidation to improve the reliability and stability of long-term operation of the absorption coating under solar radiation environment.
[0007] Compared with metal ceramics and multilayer coatings, textured surfaces have a larger diffusion area and a longer diffusion process due to their surface texture structure. Therefore, the absorption coating can withstand high temperatures for a longer time and has higher thermal stability. At present, researchers generally use catalyst technology, electrochemical treatment, hydrothermal method, ion beam etching and other processes to construct self-assembled 2D nanostructures, foam nanostructures and other textured surfaces on the surfaces of transition metals, Fe-Cr-Ni alloys, metal ceramics, etc. However, the first three have high requirements for the precision of chemical conditions, are difficult to control, and are not suitable for mass production. Ion beam etching has high requirements for equipment and requires the participation of skilled engineers, and has poor operability. Summary of the invention
[0008] The purpose of the present invention is to provide a method for preparing a textured surface spectral absorption coating with enhanced light trap effect and the coating, which can be used for high-temperature selective solar absorption coating. The method uses high-temperature annealing and oxidation reaction to cleverly borrow the element diffusion characteristics (diffusion from high concentration to low concentration), so that the elements with higher diffusion coefficients in the substrate diffuse to the substrate surface and react with oxygen to grow convex oxides on the flat substrate surface to form a natural texture surface, prolong the diffusion process, improve the absorption performance and high-temperature stability of the coating, and solve the problem 1 described in the technical background. Then, by depositing an oxide layer / nitride layer / nitride oxide layer as an anti-reflection layer, an anti-oxidation layer, and an element diffusion inhibition protective layer, the high-temperature anti-oxidation performance is further improved, and the reflectivity in the visible light range is reduced to improve the efficiency of the solar absorption coating, solving the problem 2 described in the technical background. The coating prepared by the method combines a textured surface with a protective layer, and at the same time solves the problem of structural damage caused by atomic diffusion and surface oxidation in the coating at high temperature, and improves the reliability and stability of the absorption coating in long-term operation.
[0009] In order to solve the above technical problems, the present invention adopts the following technical solutions:
[0010] In a first aspect, the present invention provides a method for preparing a textured surface spectral absorption coating for enhancing light trapping effect, comprising the following steps:
[0011] Step 1: Prepare a clean and flat substrate: Prepare a substrate, cut it into appropriate sizes, and clean it to ensure cleanliness; the substrate contains multiple elements, and the diffusion coefficients between the elements vary in a gradient, so that some elements diffuse to the surface of the substrate at high temperature;
[0012] Step 2: high temperature annealing treatment to generate a textured surface: the substrate is subjected to high temperature annealing in an oxygen environment, and annealing parameters including oxygen content, maximum annealing temperature, temperature rise rate and holding time are set to complete the preparation of the textured surface; the annealing adopts a slow-fast-slow three-step heating method;
[0013] Step 3: Deposit oxide by magnetron sputtering: Select a sputtering target, and under the action of RF power and mixed gas flow, a protective layer is deposited on the textured surface.
[0014] Furthermore, in step 1, the high diffusion elements include Si, Mn, etc. The content of high diffusion coefficient elements ranges from 0.5% to 5%. If the content is too high, it is easy to cause a large amount of elements to diffuse and destroy the basic structure of the substrate, which is not conducive to the overall stability of the solar energy absorption coating, but will lead to too high emissivity, greatly reducing the efficiency of the solar energy absorption coating. If the content is too low, the diffusible elements are too slight, and it is not easy to form protruding oxides of suitable size, and the effect of enhancing the light trap effect cannot be achieved, that is, the absorption rate is too low, and the absorption of solar radiation cannot be well achieved.
[0015] Furthermore, the substrate also includes low diffusion coefficient elements, including Fe, Cr, Ni, etc., with a content ranging from 95% to 95.5%.
[0016] Furthermore, the material of the substrate includes AISI304 stainless steel (containing elements with high diffusion coefficients such as Si and Mn) and alloy materials such as Inconel 718.
[0017] Furthermore, in step 1, the cleaning is a three-step ultrasonic cleaning method of acetone, ethanol, and deionized water, and visible oil stains, acetone residual liquid, and ethanol residue are removed in sequence, and the ultrasonic time is 3-15 minutes. The purpose of cleaning is to prevent impurities on the surface of the substrate from diffusing into the substrate during high-temperature treatment, destroying the substrate lattice and element balance, and at the same time facilitating the diffusion of elements in the substrate to the substrate surface.
[0018] Further, in step 2, annealing is performed in a muffle furnace or a tubular furnace with 0.5-10Pa flowing oxygen, the annealing temperature is between 500-1000°C, the temperature rise rate is between 2°C / min-5°C / min, and the holding time is between 30 minutes-10 hours, as follows:
[0019] Method 1: Annealing in a muffle furnace, the oxygen content in the furnace is equivalent to the atmospheric environment, and no additional oxygen is required. ① Set a lower temperature rise rate, between 2℃ / min-3℃ / min, to increase the temperature in the furnace from room temperature to a low temperature of 300℃-500℃; ② Set a higher temperature rise rate, between 3℃ / min-5℃ / min, to increase the temperature in the furnace from a low temperature of 300℃-500℃ to a medium and high temperature of 500℃-700℃; ③ Reduce the temperature rise rate, between 2℃ / min-3℃ / min, to increase the temperature in the furnace from a medium and high temperature of 500℃-700℃ to a high temperature of 700℃-1000℃; ④ Maintain the temperature in the furnace, and the insulation time is between 30 minutes and 10 hours, so that the elements with higher diffusion coefficients in the substrate can fully diffuse to the substrate surface and react with oxygen in the air to form protruding oxides.
[0020] Method 2: Annealing in a tube furnace requires additional oxygen input. ① Use a vacuum pump to make the vacuum degree in the tube reach 10 -4Pa level; ② Set a lower temperature rise rate, between 2℃ / min-3℃ / min, so that the temperature in the furnace rises from room temperature to 300℃-500℃ low temperature; ③ Set a higher temperature rise rate, between 3℃ / min-5℃ / min, so that the temperature in the furnace rises from 300℃-500℃ low temperature to 500℃-700℃ medium and high temperature; ④ Reduce the temperature rise rate, between 2℃ / min-3℃ / min, so that the temperature in the furnace rises from 500℃-700℃ medium and high temperature to 700℃-1000℃ high temperature; ⑤ Maintain the temperature in the furnace, and the insulation time is between 30 minutes ⑥ Maintain the temperature in the furnace for 30 minutes to 5 hours, and introduce 0.5-10Pa of high-purity oxygen (purity greater than or equal to 99.99%) to make the elements diffused to the substrate surface in the previous step fully react with oxygen to form a raised oxide. In addition, the oxygen flow rate is quickly increased from 0Pa to 60%-80% of the required flow rate within the first five minutes, and then slowly increased to the required flow rate within the second five minutes, and then maintained at a constant flow rate of 0.5-10Pa. In the annealing scheme in the tubular furnace, the fast-first-then-slow oxygen flow control method is to quickly put the entire environment in an oxygen atmosphere, so that oxygen molecules are fully attached to the substrate surface, and then slowly introduced to replenish the oxygen supply again, oxidize the elements on the substrate surface, and form a textured surface.
[0021] Annealing adopts a three-step heating method of slow-fast-slow. The first step, slow heating, is to preheat the annealing environment to prevent the substrate from cracking due to stress superposition caused by excessive heating rate. The second step, fast heating, can improve the annealing time. The third step, slow heating, is to better control the temperature, which is conducive to the slow diffusion of elements with higher diffusion coefficients from the substrate.
[0022] Furthermore, in step 2, high temperature promotes the diffusion of elements with higher diffusion coefficients from the high-concentration substrate to the low-concentration substrate surface, providing elemental components for the textured surface; the oxygen environment oxidizes the elements diffused to the substrate surface, forming raised bulge oxides, which become a textured surface. The texture morphology is a manifestation of the roughening of the substrate surface, which will increase the characteristic size of the coating surface. On the one hand, it enhances the light trap effect, so that the incident sunlight undergoes multiple reflections, reduces the reflectivity, and promotes spectral absorption. On the other hand, it increases the diffusion area of the coating elements, prolongs the duration of complete oxidation or structural loss of the coating, improves high temperature resistance, and solves the problem of atomic diffusion in the coating at high temperatures.
[0023] Furthermore, the textured surface morphology includes a spherical shape and a multi-plane diamond shape, and the specific morphology is achieved by regulating the element composition in the substrate, the content of high diffusion coefficient elements and annealing parameters.
[0024] Furthermore, in step 3, the sputtering target provides a metal or alloy raw material for the protective layer; the metal includes Al target, Cr target, Si target or Ti target; the alloy includes AlTi, AlCr, HfNbTaTiZr, AlCrNbSiTaTiY or AlCrNbSiTi.
[0025] Furthermore, in step 3, the magnetron sputtering parameter settings include the vacuum degree in the chamber, sample preparation temperature, radio frequency power, gas atmosphere, and deposition time.
[0026] Furthermore, the vacuum degree in the chamber is 10 -4 -10 -3 Pa level, the temperature in the chamber is between 23-300℃, the RF power is between 100-1000W, and the deposition time is between 10min-30min.
[0027] Furthermore, in step 3, the mixed gas flow is any one of an O2 / Ar mixed gas flow, an N2 / Ar mixed gas flow, and an N2 / O2 / Ar mixed gas flow, the total gas pressure is between 0.5-10Pa, the O2 / Ar ratio is between 1 / 5-5 / 1, the N2 / Ar ratio is between 1 / 5-5 / 1, and the N2 / O2 / Ar ratio is between 1 / 1 / 5-5 / 5 / 1. The three mixed gas flows are respectively used to form an oxide layer, a nitride layer, and a nitride oxide layer to solve the problem of surface oxidation of the coating at high temperature.
[0028] Furthermore, the protective layer is any one or a combination of an oxide layer, a nitride layer, and a nitride oxide layer, with a thickness between 50-1000nm, and can be used as an anti-reflection layer (reducing the reflectivity in the visible region), an anti-oxidation layer (preventing high-temperature oxidation when working in a high solar radiation environment), and a diffusion barrier layer (reducing the formation of new oxide grains).
[0029] In a second aspect, the present invention provides a textured surface spectral absorption coating with enhanced light trapping effect prepared by the method of the first aspect.
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] (1) Compared with the solar energy absorption coating of the traditional structure, the coating prepared by the present invention has novel morphology and structure. It is a combination of a rough textured surface and an oxide layer / nitride layer / nitride oxide layer protective coating. The combined effect of the two improves the absorption performance and thermal stability of the coating, and solves the problem of structural damage caused by atomic diffusion and surface oxidation in the coating at high temperature, thereby improving the high-temperature thermal stability to 800°C.
[0032] (2) The present invention cleverly utilizes the element diffusion characteristics (diffusion from high concentration to low concentration) through high temperature annealing and oxidation reaction, so that elements with higher diffusion coefficients in the substrate diffuse to the substrate surface and react with oxygen. In as little as 30 minutes, raised oxides can be grown on the flat substrate surface to form a natural textured surface.
[0033] (3) The textured surface formed by the present invention includes spherical, multi-plane diamond and other morphologies. The specific morphology is regulated by adjusting the element composition and high diffusion coefficient element content in the substrate, annealing temperature, temperature rise rate, oxygen content, annealing time and other parameters.
[0034] (4) The textured surface substrate of the present invention has spectral absorption properties by itself, and no additional absorption layer needs to be deposited. In addition, the texture morphology has greater roughness, which improves the adhesion of the coating. There is no need to worry about cracking or falling off of the protective layer due to its brittleness after high temperature.
[0035] (5) The present invention deposits an oxide layer / nitride layer / nitride oxide layer protective layer on the textured surface as an anti-reflection layer (to reduce the reflectivity in the visible region), an anti-oxidation layer (to prevent high-temperature oxidation when working in a high solar radiation environment), and a diffusion barrier layer (to reduce the formation of new oxide grains).
[0036] (6) Compared with catalyst technology, electrochemical treatment, hydrothermal method, etc., the technology of preparing textured surface in the present invention does not require complicated reaction conditions, belongs to green process, does not produce secondary hazards, has simple steps, less consumables, is controllable and repeatable, and is suitable for industrial mass production;
[0037] (7) The present invention adopts a method for preparing a coating by forming oxide protrusion particles through the diffusion effect of the substrate elements themselves in a high-temperature oxygen environment. Compared with the traditional ion beam etching method, it does not require expensive ion source equipment, has low cost, few control factors, is easy to operate and implement, is green and environmentally friendly, does not produce secondary hazards, and can be used for industrial large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 It is a schematic diagram of the substrate-coating morphology change during the preparation of the absorbing coating of the present invention; Figure 1 (a) is the original morphology of the flat substrate. Figure 1 (b) is a surface textured substrate, Figure 1 (c) a surface texture coating wrapped by a protective layer; Figure 1 In: 1- oxide grains (such as Mn3O4) formed by diffusion and oxidation of high-temperature elements, 2- oxide grains wrapped by a protective layer, 3- deposited protective layer.
[0039] Figure 2is a SEM morphology image of the substrate-coating during the coating preparation process in Example 1 of the present invention; Figure 2 (a) is the original morphology of the flat stainless steel substrate. Figure 2 (b) is a stainless steel substrate with a multi-plane diamond-like surface texture. Figure 2 (c) is a multi-plane diamond-like surface texture coating wrapped with AlCr pure alloy oxide; Figure 2 (d) is the SEM morphology of the multi-plane diamond-like surface texture coating wrapped with AlCr pure alloy oxide in Example 2 of the present invention after annealing at 800°C for 50h.
[0040] Figure 3 (a) is the reflectivity of the substrate-coating measured in the full spectrum band during the coating preparation process in Example 1 of the present invention; in FIG3(a), 4 is the reflectivity spectrum of the flat stainless steel substrate (i.e. Figure 2 (a) reflectivity spectrum); Figure 3 (a) 5 is the reflectivity spectrum of the stainless steel substrate with multi-plane diamond-like surface texture (i.e. Figure 2 (b) reflectivity spectrum); Figure 3 (a) 6 is the reflectivity spectrum of the multi-plane diamond-like surface texture absorption coating wrapped by AlCr pure alloy oxide (i.e. Figure 2 (c) Reflectance spectrum). Figure 3 (b) is the reflectivity of the multi-plane diamond-like surface texture coating wrapped by AlCr pure alloy oxide in Example 2 of the present invention measured in the full spectrum during the annealing process; Figure 3 (b) 7 is the reflectivity spectrum of the multi-plane diamond-like surface texture coating wrapped by AlCr pure alloy oxide after annealing at 800℃ for 10h; Figure 3 (b) 8 is the reflectivity spectrum of the multi-plane diamond-like surface texture coating wrapped by AlCr pure alloy oxide after annealing at 800℃ and 20h; Figure 3 (b) 9 is the reflectivity spectrum of the multi-plane diamond-like surface texture coating wrapped by AlCr pure alloy oxide after annealing at 800℃ for 50h (i.e. Figure 2 (d) Reflectance spectrum).
[0041] Figure 4 is the SEM morphology image and element distribution of the textured surface prepared in Example 3 of the present invention; Figure 4 (a) is the SEM morphology image of the textured surface. Figure 4 (b) is the Mn element distribution diagram of the textured surface. Figure 4 (c) is the O element distribution map of the textured surface. DETAILED DESCRIPTION
[0042] The technical solutions in the embodiments of the present invention will be described clearly and completely below in combination with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0043] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments may be combined with each other.
[0044] The present invention provides a method for preparing a textured surface spectral absorption coating with enhanced light trap effect and the coating, which can be used for high-temperature selective solar absorption coating. A surface with a textured structure is prepared by high-temperature annealing and radio frequency magnetron sputtering, and then an oxide layer / nitride layer / nitride oxide layer is deposited as a protective layer and an anti-reflection layer. The textured surface prolongs the diffusion process, improves the absorption performance and high-temperature stability, and the oxide layer / nitride layer / nitride oxide layer improves the oxidation resistance of the coating and reduces the reflectivity in the visible light range, so as to improve the efficiency of the solar absorption coating and meet the requirements of the new generation of concentrated solar energy system technology.
[0045] Figure 1 The process of coating preparation is shown, and the specific preparation method includes the following steps:
[0046] Step 1: Prepare a clean and flat substrate: Prepare the required substrate, cut it into appropriate sizes, and clean it with acetone, ethanol, and deionized water to remove contaminants, such as Figure 1 (a).
[0047] Step 2: High temperature annealing treatment to generate a textured surface: Place the substrate in a muffle furnace or a tube furnace in an oxygen atmosphere, set parameters such as oxygen content, maximum annealing temperature, temperature rise rate, and holding time to complete the preparation of the textured surface, as shown in Figure 1(b).
[0048] Step 3: Deposit oxide by magnetron sputtering: Select a suitable sputtering target, and under the action of RF power and mixed gas flow, deposit a protective layer on the textured surface as an anti-reflection layer, anti-oxidation layer, and element diffusion inhibition protective layer, as shown in Figure 1(c).
[0049] Furthermore, in step 1, the substrate is usually selected to contain multiple elements and needs to contain high diffusion elements such as Si and Mn, and the diffusion coefficients between the elements are gradient-varying, so that some elements can diffuse to the substrate surface at high temperature. Preferably, the substrate material is selected from AISI304 stainless steel (containing elements with high diffusion coefficients such as Si and Mn), Inconel 718, etc. The diffusion coefficients between the elements are gradient-varying, that is, the diffusion coefficients of the multiple elements are different, which will make the elements with high diffusion coefficients diffuse to the substrate surface at a certain temperature, while the elements with low diffusion coefficients maintain their original positions.
[0050] Furthermore, the content of high diffusion coefficient elements contained in the substrate should not be too high, and should be between 0.5% and 5%. If it is too high, it will easily lead to the diffusion of a large number of elements and destroy the basic structure of the substrate, which is not conducive to the overall stability of the solar energy absorption coating. Instead, it will lead to excessively high emissivity, greatly reducing the efficiency of the solar energy absorption coating. If it is too low, the diffusible elements are too slight and it is not easy to form protruding oxides of suitable sizes, which cannot achieve the effect of enhancing the light trap effect, that is, the absorption rate is too low and the absorption of solar radiation cannot be well achieved.
[0051] Furthermore, the substrate also includes low diffusion coefficient elements, including Fe, Cr, Ni, etc., with a content ranging from 95% to 95.5%.
[0052] Furthermore, in step 1, the cleaning is a three-step ultrasonic cleaning method of acetone, ethanol, and deionized water, which removes visible oil stains, acetone residual liquid, and ethanol residual in sequence, and the ultrasonic time is 3-15 minutes.
[0053] Furthermore, the purpose of cleaning in step 1 is to prevent impurities on the substrate surface from diffusing into the substrate during high-temperature treatment, thereby destroying the substrate lattice and element balance, and to facilitate the diffusion of elements in the substrate to the substrate surface.
[0054] Furthermore, in step 2, the annealing treatment means should have both high temperature and oxygen environment, the temperature is between 500-1000°C, the temperature rise rate is between 2°C / min-5°C / min, a muffle furnace can be selected, and the substrate will be annealed in natural air, or a tubular furnace can be selected, and 0.5-10Pa of flowing high-purity oxygen is introduced to artificially create an oxygen atmosphere, and the insulation time is between 30 minutes-10 hours.
[0055] Method 1: Annealing in a muffle furnace, the oxygen content in the furnace is equivalent to the atmospheric environment, and no additional oxygen is required. ① Set a lower temperature rise rate, between 2℃ / min-3℃ / min, to increase the temperature in the furnace from room temperature to a low temperature of 300℃-500℃; ② Set a higher temperature rise rate, between 3℃ / min-5℃ / min, to increase the temperature in the furnace from a low temperature of 300℃-500℃ to a medium and high temperature of 500℃-700℃; ③ Reduce the temperature rise rate, between 2℃ / min-3℃ / min, to increase the temperature in the furnace from a medium and high temperature of 500℃-700℃ to a high temperature of 700℃-1000℃; ④ Maintain the temperature in the furnace, and the insulation time is between 30 minutes and 10 hours, so that the elements with higher diffusion coefficients in the substrate can fully diffuse to the substrate surface and react with oxygen in the air to form protruding oxides.
[0056] Method 2: Annealing in a tube furnace requires additional oxygen input. ① Use a vacuum pump to make the vacuum degree in the tube reach 10 -4 Pa level; ② Set a lower temperature rise rate, between 2℃ / min-3℃ / min, so that the temperature in the furnace rises from room temperature to 300℃-500℃ low temperature; ③ Set a higher temperature rise rate, between 3℃ / min-5℃ / min, so that the temperature in the furnace rises from 300℃-500℃ low temperature to 500℃-700℃ medium and high temperature; ④ Reduce the temperature rise rate, between 2℃ / min-3℃ / min, so that the temperature in the furnace rises from 500℃-700℃ medium and high temperature to 700℃-1000℃ high temperature; ⑤ Maintain the temperature in the furnace, and the insulation time is between 30 minutes ⑥ Maintain the temperature in the furnace for 30 minutes to 5 hours, and at the same time introduce 0.5-10Pa of flowing high-purity oxygen (purity greater than or equal to 99.99%) to allow the elements diffused to the substrate surface in the previous step to fully react with the oxygen to form a raised oxide. In addition, the oxygen flow rate is rapidly increased from 0Pa to 60%-80% of the required flow rate within the first five minutes, and then slowly increased to the required flow rate within the second five minutes, and then maintained at a constant flow rate of 0.5-10Pa.
[0057] In step 2, the role of the high temperature environment is that there is a concentration gradient between the substrate surface and the substrate. The high temperature will promote the diffusion of elements with higher diffusion coefficients from the high-concentration substrate to the low-concentration substrate surface, providing elemental components for the textured surface. The slow-fast-slow three-step heating method, the first step of slow heating, is to preheat the annealing environment to prevent the substrate from cracking due to stress superposition caused by excessive heating speed. The second step of fast heating can improve the annealing time. The third step of slow heating is to better control the temperature, which is conducive to the slow diffusion of elements with higher diffusion coefficients from the substrate.
[0058] In step 2, the oxygen atmosphere is used to oxidize the elements diffused to the surface of the substrate, forming a raised bulge oxide, which becomes a textured surface and solves the problem of atomic diffusion in the coating at high temperature. For the annealing scheme in the tube furnace, the oxygen flow control method of fast first and then slow is to make the whole environment quickly in the oxygen atmosphere, so that the oxygen molecules are fully attached to the surface of the substrate, and then slowly introduced to replenish the oxygen supply again, oxidize the elements on the surface of the substrate, and form a textured surface.
[0059] Furthermore, in step 2, the textured surface formed after the diffusion and oxidation reaction includes spherical, multi-plane diamond and other morphologies. The specific morphology is controlled by adjusting parameters such as the element composition and high diffusion coefficient element content in the substrate, annealing temperature, temperature rise rate, oxygen content, and annealing time. The texture morphology is a manifestation of the roughening of the substrate surface, which will increase the characteristic size of the coating surface. On the one hand, it enhances the light trap effect, causing the incident sunlight to experience multiple reflections, reduce reflectivity, and promote spectral absorption. On the other hand, it increases the diffusion area of the coating elements, prolongs the duration of complete oxidation or structural loss of the coating, improves high temperature resistance, and solves the problem of atomic diffusion in the coating at high temperatures.
[0060] Furthermore, in step 3, the sputtering target provides a raw material of metal or alloy for the protective layer, which may be a metal target such as Al target, Cr target, Si target, Ti target, an alloy target such as AlTi, AlCr, or a high entropy alloy target such as HfNbTaTiZr, AlCrNbSiTaTiY, AlCrNbSiTi.
[0061] Furthermore, in step 3, the magnetron sputtering parameter settings include the vacuum degree in the chamber, sample preparation temperature, radio frequency power, gas atmosphere, and deposition time.
[0062] Furthermore, the vacuum degree in the cavity is 10 -4 -10 -3 Pa level, and the temperature inside the cavity is between 23-300℃.
[0063] Furthermore, the radio frequency power is between 100-1000W.
[0064] Furthermore, the protective layer can be any one or a combination of an oxide layer, a nitride layer, and a nitride oxide layer, with a thickness between 50-1000nm, and can be used as an anti-reflection layer (reducing the reflectivity in the visible region), an anti-oxidation layer (preventing high-temperature oxidation when working in a high solar radiation environment), and a diffusion barrier layer (reducing the formation of new oxide grains) to solve the problem of coating surface oxidation at high temperatures.
[0065] Furthermore, the gas atmosphere can be any one of an O2 / Ar mixed gas flow, a N2 / Ar mixed gas flow, and a N2 / O2 / Ar mixed gas flow, with a total gas pressure between 0.5-10Pa, an O2 / Ar ratio between 1 / 5-5 / 1, an N2 / Ar ratio between 1 / 5-5 / 1, and an N2 / O2 / Ar ratio between 1 / 1 / 5-5 / 5 / 1, and the three mixed gas flows are used to form an oxide layer, a nitride layer, and a nitride oxide layer, respectively.
[0066] Furthermore, the high temperature stability of the prepared coating was verified by annealing in a high temperature annealing furnace and conducting a thermal stability test in air. During the annealing process, samples were taken out regularly for morphology measurement and optical property characterization.
[0067] Thermal stability test, temperature between 600-1000℃, time between 1 hour and 2000 hours. Morphological measurement includes SEM micromorphology characterization and AFM surface roughness analysis.
[0068] The optical performance is characterized by measuring the coating reflectivity R in the full spectrum band of 0.3-25μm, and then calculating the absorptivity α in the solar spectrum band, the self-thermal emissivity ε in the infrared band and the spectral absorption selectivity α / ε, and the PC value of the performance change before and after annealing.
[0069] The conversion formula of coating absorptivity and reflectivity in the solar spectrum band (0.3-2.5μm):
[0070]
[0071] The conversion formula of the coating's own thermal emissivity and reflectivity in the infrared band (2.5-25μm):
[0072]
[0073] PC value: PC = -Δα + 0.5Δε, PC value is the quantitative value of performance attenuation. The larger the PC value, the greater the impact of annealing on the coating, the worse the thermal stability of the optical absorption performance, and the negative PC value indicates that the optical absorption performance is enhanced after annealing. The maximum acceptable PC value is 0.05.
[0074] In the above formula, R, α, and ε are reflectivity, absorptivity, and thermal emissivity, respectively. It can be seen that the higher the reflectivity R, the lower the coating absorptivity α and thermal emissivity ε. λ is the wavelength of solar or thermal radiation, I sol (λ) is the solar radiation under AM1.5, R(λ) is the spectral reflectance, I b (λ) is the spectral thermal emissivity of an absolute black body at room temperature.
[0075] The present invention will be further described below in conjunction with specific examples, but they are not intended to be limiting of the present invention.
[0076] Example 1
[0077] The present embodiment provides a method for preparing a textured surface spectral absorption coating with enhanced light trap effect and the coating, wherein the textured surface is formed by high-temperature diffusion and oxidation reaction, and the morphology of the prepared textured surface is adjustable, and the specific morphology is controlled by regulating parameters such as the element composition and high diffusion coefficient element content in the substrate, annealing temperature, temperature rise rate, oxygen content, and annealing time.
[0078] Combination Figure 2 (a)-(c), 3(a), taking the preparation of a spectral absorption coating with a multi-plane diamond-like textured surface, stainless steel as the substrate and absorption layer, and AlCr oxide as the protective layer as an example to illustrate.
[0079] Step 1: Prepare a clean and flat substrate: Prepare the required AISI304 stainless steel substrate (Mn content is 1.5%), cut it into 3cm×4cm blocks, and wash it with acetone, ethanol, and deionized water respectively, each for 10 minutes.
[0080] Step 2: High temperature annealing treatment to generate a textured surface: Place the AISI304 stainless steel substrate in a muffle furnace, set the temperature rise rates of the slow-fast-slow three-step heating method to 3℃ / min, 5℃ / min, and 3℃ / min, respectively, and increase them to 300℃, 600℃, and 800℃ respectively. The maximum annealing temperature is 800℃, and the holding time is 1 hour to complete the textured surface preparation.
[0081] Step 3: Deposition of oxide by magnetron sputtering: AlCr sputtering target was selected, and the vacuum degree was 2×10 -3 Pa, sample preparation temperature is 150℃, RF power is 800W, gas atmosphere is O2 / Ar mixed gas flow, total gas pressure is 2.5Pa, O2 / Ar ratio is 1 / 2, and deposition time is 40min. Under the action of RF power supply and mixed gas flow, a layer of AlCrO protective layer is deposited on the textured surface as an anti-reflection layer, anti-oxidation layer, and element diffusion inhibition protective layer.
[0082] The surface morphology is measured by scanning electron microscope (SEM), the surface element composition is measured by energy dispersive spectrometer (EDS), and the crystal structure is measured by X-ray diffractometer (XRD). Figure 2 As shown, Figure 2 (a) is the original morphology of the flat stainless steel substrate. Figure 2 (b) is a stainless steel substrate with a multi-plane diamond-like surface texture. Figure 2 (c) is a multi-plane diamond-like surface texture coating wrapped with pure AlCr alloy oxide. The average surface roughness of the three is 19nm, 134nm, and 110nm respectively. Figure 2It can be seen that the surface of the stainless steel after annealing at 800℃ for 1h is no longer flat, but is composed of many multi-plane diamond-like particles with characteristic sizes ranging from 100nm to 1μm, such as Figure 2 (b) As shown; EDS and XRD analysis show that the particles are Mn3O4 grains, which means that the presence of high temperature environment and oxidation conditions is conducive to promoting the diffusion of Mn elements in the AISI304 stainless steel substrate to the substrate surface and oxidation to form Mn3O4 grains, completing the preparation of the textured surface. The pure alloy oxide AlCrO coating is about 60nm, wrapped on the textured surface, and its SEM morphology is shown in Figure 2 As shown in (c), the feature size is increased to 400nm-1μm.
[0083] Reflectance spectrum Figure 3 (a) Figure 3 (a) 4 is the reflectivity spectrum of a flat stainless steel substrate (i.e. Figure 2 (a) Reflectivity spectrum), the absorptivity, thermal emissivity, and absorption ratio are 0.362, 0.135, and 2.68, respectively; Figure 3 (a) 5 is the reflectivity spectrum of the stainless steel substrate with multi-plane diamond-like surface texture (i.e. Figure 2 (b) Reflectivity spectrum), the absorptivity, thermal emissivity, and absorption ratio are 0.843, 0.143, and 5.90, respectively; Figure 3 (a) 6 is the reflectivity spectrum of the multi-plane diamond-like surface texture absorption coating wrapped by AlCr pure alloy oxide (i.e. Figure 2 (c) Reflectivity spectrum), the absorptivity, thermal emissivity, and absorption ratio are 0.854, 0.160, and 5.34, respectively. Figure 3 It can be seen that the absorption performance of the textured surface is better than that of the flat stainless steel substrate, and the spectral absorptivity is improved to a great extent, proving that this multi-plane diamond-like surface morphology can enhance the absorption performance of the coating and enhance the light trap effect. After being wrapped with a layer of AlCr oxide, the coating has anti-reflection properties and the absorptivity is further increased, which further improves the optical properties of the absorption layer.
[0084] Example 2
[0085] Combination Figure 2 (d) Figure 3 (b) Based on Example 1, the high temperature stability of the multi-plane diamond-shaped surface textured solar selective absorption coating with stainless steel as the substrate and absorption layer and AlCr oxide as the protective layer and anti-reflection layer was further verified.
[0086] The high temperature stability of the coating prepared in Example 1 was verified by annealing in a high temperature annealing furnace at 800° C. and conducting a thermal stability test in air. During the annealing process, samples were taken out at 10, 20, and 50 hours for morphology measurement and optical property characterization.
[0087] SEM surface morphology Figure 2 (d) Figure 2 (d) is the morphology of the multi-plane diamond-like surface texture coating wrapped with AlCr pure alloy oxide after annealing at 800℃ and 50h. The average surface roughness is 143nm. The morphology does not change much after annealing at 800℃ and 50h, which means that the multi-plane diamond-like surface texture coating wrapped with AlCr pure alloy oxide has good structural stability at 800℃.
[0088] Reflectance spectrum Figure 3 (b) Figure 3 (b) 7 is the reflectivity spectrum of the multi-plane diamond-like surface texture coating wrapped by AlCr pure alloy oxide after annealing at 800℃ for 10h. The absorptivity, thermal emissivity, absorption ratio and PC values are 0.838, 0.165, 5.08 and 0.019 respectively; Figure 3 (b) 8 is the reflectivity spectrum of the multi-plane diamond-like surface texture coating wrapped by AlCr pure alloy oxide after annealing at 800℃ for 20h. The absorptivity, thermal emissivity, absorption ratio and PC values are 0.840, 0.164, 5.12 and 0.016 respectively; Figure 3 (b) 9 is the reflectivity spectrum of the multi-plane diamond-like surface texture coating wrapped by AlCr pure alloy oxide after annealing at 800℃ for 50h (i.e. Figure 2 (d) reflectivity spectrum), the absorptivity, thermal emissivity, absorption ratio, and PC values are 0.867, 0.172, 5.04, and -0.007, respectively. It can be seen that the reflectivity spectrum changes little before and after annealing, the absorptivity, thermal emissivity, and absorption ratio are very stable, and the PC value is very low, which means that annealing has little effect on the coating, and the thermal stability of the optical absorption performance is very good. After annealing at 800°C and 50h, the PC value is lower than zero, indicating that the optical absorption performance of the coating is enhanced. Experiments have shown that the rough texture surface of the coating effectively increases the diffusion area and process, and the coating is able to maintain the original absorption performance of the spectrum at high temperatures. AlCr oxide has good high-temperature stability. Its presence further protects the stainless steel texture surface from oxidation at high temperatures. The multi-plane diamond-shaped surface texture absorption coating containing the AlCr oxide layer has a high-temperature stability of 800°C. In order to illustrate the effect of the present invention, Table 1 gives the optical parameters of each sample in Example 1 and Example 2.
[0089] Table 1 Optical parameters of each sample
[0090]
[0091] Example 3
[0092] Combination Figure 4, annealing was performed in a vacuum tube furnace to prepare a textured oxide surface.
[0093] Step 1: Prepare a clean and flat substrate: Prepare the required AISI304 stainless steel substrate (Mn content is 1.5%), cut it into 3cm×4cm blocks, and wash it with acetone, ethanol, and deionized water respectively, each for 10 minutes.
[0094] Step 2: High temperature annealing treatment to generate textured surface: AISI304 stainless steel substrate was placed in a vacuum tube furnace with a vacuum degree of 6×10 -4 Pa, the temperature rise rate of the slow-fast-slow three-step heating method was set to 3℃ / min, 5℃ / min, and 3℃ / min, respectively, and then increased to 300℃, 500℃, and 700℃, respectively. The highest annealing temperature was 700℃, and the holding time was 2 hours to complete the texture surface preparation. After the temperature was raised to 700℃ and kept for 0.5 hours, oxygen was input by the oxygen flow control method of first fast and then slow. The oxygen flow rate was quickly increased from 0Pa to 4Pa in the first five minutes, and then slowly increased to 5Pa in the second five minutes, and maintained at a constant condition of 700℃ and 5Pa for annealing for 1.5 hours.
[0095] The surface morphology is measured by SEM, and the surface element composition and distribution are measured by EDS. Figure 4 As shown in (a), the surface of the stainless steel after annealing at 700℃, 2h, and 5Pa oxygen flow is no longer flat, but is composed of many multi-plane diamond-like particles with characteristic sizes ranging from 1μm to 6μm. EDS analysis shows that the distribution of Mn and O elements on the textured surface is as follows: Figure 4 (b), 4 (c) (the brighter and whiter the light spot is, the higher the content of Mn or O is). It can be seen that the textured area is enriched with Mn and O elements, indicating that the formed particles are manganese oxide grains, which means that the existence of high temperature environment and oxidation conditions is conducive to promoting the diffusion of Mn elements in the AISI304 stainless steel substrate to the substrate surface and oxidation to form manganese oxide grains, completing the preparation of the textured surface.
[0096] The above are only preferred embodiments of the present invention, and are not intended to limit the implementation methods and protection scope of the present invention. Those skilled in the art should be aware that all solutions obtained by equivalent substitutions and obvious changes made using the contents of the specification of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a textured surface spectral absorption coating for enhancing light trapping effect, characterized in that: The following steps are involved: Step 1: Prepare a clean and flat substrate: Prepare a substrate, cut it into appropriate sizes, and clean it to ensure cleanliness; the substrate contains multiple elements and must contain elements with high diffusion coefficients, and the diffusion coefficients between elements vary in a gradient, so that some elements can diffuse to the substrate surface at high temperatures; Step 2: high temperature annealing treatment to generate a textured surface: the substrate is subjected to high temperature annealing in an oxygen environment, and annealing parameters including oxygen content, maximum annealing temperature, temperature rise rate and holding time are set to complete the preparation of the textured surface; the annealing adopts a slow-fast-slow three-step heating method; In the step 2, annealing is performed in a muffle furnace or a tubular furnace with oxygen, the annealing temperature is between 500-1000° C., the temperature rise rate is between 2° C. / min-5° C. / min, and the holding time is between 30 minutes-10 hours; Method 1: Annealing in a muffle furnace, the oxygen content in the furnace is equivalent to the atmospheric environment, and no additional oxygen is required. ① Set a lower temperature rise rate, between 2℃ / min-3℃ / min, so that the temperature in the furnace rises from room temperature to a low temperature of 300℃-500℃; ② Set a higher temperature rise rate, between 3℃ / min-5℃ / min, so that the temperature in the furnace rises from a low temperature of 300℃-500℃ to a medium and high temperature of 500℃-700℃; ③ Reduce the temperature rise rate, between 2℃ / min-3℃ / min, so that the temperature in the furnace rises from a medium and high temperature of 500℃-700℃ to a high temperature of 700℃-1000℃; ④ Maintain the temperature in the furnace, and the insulation time is between 30 minutes and 10 hours, so that the elements with higher diffusion coefficients in the substrate are fully diffused to the substrate surface and react with oxygen in the air to form protruding oxides; Method 2: Annealing in a tube furnace requires additional oxygen input. ① Use a vacuum pump to make the vacuum degree in the tube reach 10 - 4 Pa level; ② set a lower temperature rise rate, between 2℃ / min-3℃ / min, so that the temperature in the furnace rises from room temperature to 300℃-500℃ low temperature; ③ set a higher temperature rise rate, between 3℃ / min-5℃ / min, so that the temperature in the furnace rises from 300℃-500℃ low temperature to 500℃-700℃ medium and high temperature; ④ reduce the temperature rise rate, between 2℃ / min-3℃ / min, so that the temperature in the furnace rises from 500℃-700℃ medium and high temperature to 700℃-1000℃ high temperature; ⑤ maintain the temperature in the furnace, and the insulation time is between 30 ⑥ Maintain the temperature in the furnace for 30 minutes to 5 hours, and at the same time introduce 0.5-10Pa of flowing high-purity oxygen (purity greater than or equal to 99.99%), so that the elements diffused to the surface of the substrate in the previous step react with the oxygen to form a raised oxide. In addition, the oxygen flow rate is first rapidly increased from 0Pa to 60%-80% of the required flow rate within the first five minutes, and then slowly increased to the required flow rate within the second five minutes, and then maintained at a constant flow rate of 0.5-10Pa; Step 3: Deposition of oxide by magnetron sputtering: Select a sputtering target and deposit a protective layer on the textured surface under the action of RF power and mixed gas flow.
2. The preparation method according to claim 1, characterized in that: In the step 1, the high diffusion coefficient elements include Si and Mn, with a content range of 0.5%-5%, and the elements of the substrate also include low diffusion coefficient elements, including Fe, Cr, and Ni, with a content range of 95%-95.5%.
3. The preparation method according to claim 2, characterized in that: The materials of the substrate include AISI304 stainless steel and Inconel 718.
4. The preparation method according to claim 1, characterized in that: In step 2, high temperature promotes the diffusion of elements with higher diffusion coefficients from the high-concentration substrate to the low-concentration substrate surface, providing elemental components for the textured surface; the oxygen environment oxidizes the elements diffused to the substrate surface to form raised oxide bumps, which become the textured surface; the textured surface morphology includes spherical and multi-plane diamond shapes, and the specific morphology is achieved by regulating the element composition in the substrate, the content of high diffusion coefficient elements and the annealing parameters.
5. The preparation method according to claim 1, characterized in that: In step 3, the sputtering target provides metal or alloy raw materials for the protective layer; the metal includes Al target, Cr target, Si target or Ti target; the alloy includes AlTi, AlCr, HfNbTaTiZr, AlCrNbSiTaTiY or AlCrNbSiTi.
6. The preparation method according to claim 1, characterized in that: In step 3, the magnetron sputtering parameter settings include the vacuum degree in the chamber, sample preparation temperature, RF power, gas atmosphere, and deposition time; the vacuum degree in the chamber is 10 -4 -10 -3 Pa level, the temperature in the chamber is between 23-300℃, the RF power is between 100-1000W, and the deposition time is between 10min-30min.
7. The preparation method according to claim 1, characterized in that: In step 3, the mixed gas flow is any one of an O2 / Ar mixed gas flow, an N2 / Ar mixed gas flow, and an N2 / O2 / Ar mixed gas flow, the total gas pressure is between 0.5-10Pa, the O2 / Ar ratio is between 1 / 5-5 / 1, the N2 / Ar ratio is between 1 / 5-5 / 1, and the N2 / O2 / Ar ratio is between 1 / 1 / 5-5 / 5 / 1, and the three mixed gas flows are used to form an oxide layer, a nitride layer, and a nitride oxide layer, respectively.
8. The preparation method according to claim 1, characterized in that: The protective layer is any one or a combination of an oxide layer, a nitride layer, and a nitride oxide layer, and has a thickness of 50-1000 nm.
9. A textured surface spectral absorption coating for enhancing light trapping effect, characterized in that: The method according to any one of claims 1 to 8 is used to prepare the product.
Citation Information
Patent Citations
Inoxidizability solar spectrum selective absorbing coating and preparation method thereof
CN103162452A
Novel nano-composite solar spectral selective absorption coating and preparation method thereof
CN109724274A